PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN (PKn) MELALUI PENDEKATAN COOPERATIVE LEARNING TIPE JIGSAW - Manurung, Marince (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This research background by researcher observations in class VI SDN 26 Bahagia Panti. The purpose of this study is to describe the design, execution, and learning outcomes in learning PKN. The study was conducted in two cycles and three meetings, and subjects were sixth grade students of SDN 26 Bahagia  Panti which consists of 8 men and 10 women. Data collected through observations, field notes, and evaluations. Thus evident that the cooperative learning approach jigsaw type can improve student learning outcomes in the classroom learning PKN VI SDN 26 Bahagia Panti Pasaman district nursing. Kata kunci : PKn, hasil belajar, dan melalui pendekatan cooperative learning type jigsaw